Réponses

Meilleure réponse !
2014-03-09T00:05:49+01:00
Bonsoir

1) g(x) = (1 - x)(x + 1)² = (1 - x)(x² + 2x + 1)
                                = x² + 2x + 1 - x^3 - 2x² - x
                                = -x^3 - x² + x + 1

2) g'(x) = -3x² - 2x + 1

3) Signe de g'(x).

Racines de -3x² - 2x + 1

\Delta = (-2)^2-4\times(-3)\times1=4+12=16\\\\x_1=\dfrac{2-\sqrt{16}}{-6}=\dfrac{1}{3}\\\\x_2=\dfrac{2+\sqrt{16}}{-6}=-1

\begin{array}{|c|ccccccc||}x&-2&&-1&&\dfrac{1}{3}&&1\\\ g'(x)=-3x^2-2x+1&&-&0&+&0&-&\\ g(x)&3&\searrow&0&\nearrow&\dfrac{32}{27}&\searrow&0 \\\end{array}

Donc g est décroissante sur [-2 ; -1] U [1/3 ; 1]
        g est croissante sur [-1 ; 1/3]